The Image of Women in the Main Character of the Novel Jais Darga Namaku by Ahda Imran: A Feminist Approach - Nurseha -; Parlaungan Ritonga; Bambang Riyanto (Bahasa Indonesia Prima, 2025)
Literary works are very influential in human life because they contain messages and lessons that can be taken for life. Novels are literary works with various themes, including social issues that generally occur in society, including those related to the image of women. This research aims to describe the image of women in the novel Jais Darga Namaku by Ahda Imran using a feminist approach with Sugihastuti's theory that focuses on two main aspects in the form of women's self-image and women's social image of the main character, Jais Darga. The data source in this research uses the novel Jais Darga Namaku by Ahda Imran, published by Gramedia in 2022. This research was conducted using a descriptive qualitative method. The data presented are words, phrases, sentences, or paragraphs that contain images of women. The data collection technique used document analysis by reading, recording, classifying, and describing. The results of the study can be concluded that the image of women in the novel Jais Darga Namaku by Ahda Imran includes (1) Women's self-image from the physical aspects of puberty, menstruation, pregnancy, childbirth, and psychological aspects that have humility, intelligence, independence, resilience, and self-confidence, and (2) The social image of women in the family through their role as independent and forgiving wives and mothers and the social image of women in society as successful women in the international art world.